Is a Decentralised Health Policy Associated With Better Self-rated Health and Health Services Evaluation? A Comparative Study of European Countries - Pål E. Martinussen; Håvard T. Rydland (Kerman University of Medical Sciences, 2021)
Background While decentralisation has come to be a major policy strategy in many healthcare systems, there is still insufficient evidence about its impact. Most studies have been of developing countries, and they have provided mixed results. This study is the first to test the relevance of political decentralisation across European countries, thus meeting the demand for more studies of decentralisation in developed countries, and building on an indicator of decentralisation reflecting the allocation of authority for both health policy tasks and health policy areas.   Methods As indicators of health system outcome, we employed 2 measures that have not previously been investigated in the context of decentralisation: self-rated health and satisfaction with healthcare system. Using multilevel modelling and controlling for individual-level demographic and socioeconomic variables, the paper utilised the 2014 (7th) and 2016 (8th) round of the European Social Survey (ESS), including more than 70 000 individuals from 20 countries.   Results The results suggest that decentralisation has a positive and significant association with health system satisfaction, but not with self-rated health. Of the different operationalisations, decentralised healthcare provision had the strongest association with health system satisfaction.   Conclusions Our study fails to provide clear support for decentralised health systems. There is a need for more research on the impact of such reforms in order to provide policy-makers with knowledge of desirable governance, organisational designs, management and incentives in healthcare.